Absorption Rate of Industrial Program Vocational High School Students to the World of Work - Mulyanto; Eko Nugroho Widodo (Journal for Lesson and Learning Studies)
The development of industrial technology today is very fast. However, vocational high schools as a workforce generator do not have good readiness to meet the needs of the industrial world of work. This study aims to analyze the planning, implementation, evaluation, and absorption of students in the industrial class. This study used a qualitative approach with interview, observation, and documentation techniques. Data analysis includes two things, namely the implementation of analysis before in the field and analysis during the field. The results showed that industrial class planning had been carried out well, with curriculum synchronization, street vendors students, apprentice teachers, and guest teachers. Evaluation of activities is carried out periodically once a year. Student absorption in the 1st vocational school industry reaches 94% at PT Alfamart, while the 2nd vocational school is only absorbed 50%, with 30% at PT Daihatsu and 20% in other industries. Thus, the industrial class program at vocational school has been successfully implemented properly. The implication of the results of this research is that stakeholders, such as schools, government and industry, can work together to improve vocational education and increase job opportunities for vocational school graduates.